Multi-scale modelling of rafting behaviour under complex stress states for Ni3Al superalloys. (May 2022) - Li, R.Z.; Xie, B.; Yang, X.G.; Fan, Y.S.; Sun, Y.T.; Shi, D.Q.
Highlights: An atomistic representative cell of γ'/γ structure in Ni3 Al superalloys is constructed to simulate the dislocation motions under different stress states. An energy-based orientation criterion of rafting is proposed for complex stress states based on the MD results, which is validated by the experiments in the literature. A thermodynamic rafting model based on the energy dissipation theory coupling with crystal plasticity constitutive relations was proposed to predict the variation law of microstructural features. Abstract: Directional coarsening behaviour, also known as rafting, largely determines the mechanical properties of Ni3 Al superalloys. However, owing to a vague understanding of the micro-scale mechanisms of the superalloys, modelling their rafting behaviour is still challenging, especially under complex stress states. The present work aims to predict rafting behaviours under complex stress states through macro-scale thermodynamic approaches assisted by micro-scale molecular dynamics. First, an atomistic representative cell of the γ'/γ structure in the Ni3 Al superalloy was constructed to simulate the dislocation motion and elastic and dislocation energy distribution in the γ matrix channels under different stress states at the initial rafting stage. Accordingly, an energy-based orientation criterion was proposed for the rafting behaviour under complex stress states. The criterion was then applied to a thermodynamic system of the γ'/γ structure to model the rafting behaviour on the basis of energy dissipation theory coupled with crystal plasticity constitutive relations. The new rafting model was verified by the experimental observations in the literature and was used to evaluate the effects of temperature and stress states on rafting. This research offers a basic understanding of the directional coarsening and provides a prediction tool for the direction and variation law of the rafting process.